2003
DOI: 10.1071/wr02029
|View full text |Cite
|
Sign up to set email alerts
|

Koala mortality on roads in south-east Queensland: the koala speed-zone trial

Abstract: In 1995, the Queensland Parks and Wildlife Service, the Queensland Department of Main Roads and Redland Shire Council initiated the Koala Speed Zone Trial in the Koala Coast, south-east Queensland. The aim of the trial was to assess the effect of differential speed signs on the number of koalas (Phascolarctos cinereus) hit by vehicles in the Koala Coast from 1995 to 1999. On the basis of information collected by the Queensland Parks and Wildlife Service 1407 koalas were hit by vehicles in the Koala Coast durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 0 publications
8
110
1
Order By: Relevance
“…Our findings are consistent with other studies that have shown a high probability of trauma for koalas moving in and through fragmented and heavily urbanised areas in south-east Queensland (e.g. Dique et al 2003aDique et al , 2003c. One of the koalas that was killed by a train (F2) had crossed the rail line by climbing over chainwire fencing while a safe underpass under the rail line for pedestrians was within metres of the animal's crossing point.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our findings are consistent with other studies that have shown a high probability of trauma for koalas moving in and through fragmented and heavily urbanised areas in south-east Queensland (e.g. Dique et al 2003aDique et al , 2003c. One of the koalas that was killed by a train (F2) had crossed the rail line by climbing over chainwire fencing while a safe underpass under the rail line for pedestrians was within metres of the animal's crossing point.…”
Section: Discussionsupporting
confidence: 82%
“…Koala populations in south-east Queensland are experiencing rapid reductions in range (Dique et al 2003a(Dique et al , 2004. This decline has mostly been attributed to habitat fragmentation (Martin and Handasyde 1999) and loss through clearing for agriculture and urban development (Cogger et al 2003;Sullivan et al 2004;Gordon et al 2006;Lane 2008;DERM 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite warning signs being commonly used, there is little evidence that they significantly change driver behaviour and reduce road-kill rates (Dique et al 2003;Al-Ghamdi and AlGadhi 2004). Standard kangaroo warning signs were ineffective at reducing macropod road-kill rates immediately following erection along the Northern Highway in central Victoria in 1978 (Coulson 1982).…”
Section: Wildlife Warning Signsmentioning
confidence: 99%